THE INFLUENCE OF SOLVENCY AND LIQUIDITY ON STOCK RETURNS WITH PROFITABILITY AS A MODERATION VARIABLE IN BANKING COMPANIES (Jurnal Ipteks Terapan, 2023)
This research aims to determine the effect of solvency and liquidity on stock returns with profitability as a moderating variable in banking companies listed on the IDX for the 2017-2021 period. This research uses quantitative methods. The population in this study were all banking companies registered on the IDX for the 2017 - 2021 period. The sample in this study used a purposive sampling method so that a total sample of 15 companies was obtained. The type of data used is secondary data obtained from www.idx.com and www.investing.com . The analytical method used is multiple regression analysis using Eviews version 10. The results of this research show that solvency as proxied by the Debt to Euity Ratio has no effect on stock returns. Liquidity as proxied by the Current Ratio has a positive and significant effect on stock returns. Profitability as proxied by Return on Assets is unable to mediate the effect of solvency on stock returns. Profitability is able to mediate the effect of liquidity on stock returns